Optimizing Public Relations Activities Through The Race Model - Nuriyati Samaatan; Irfan Fauzi; Meranti Meranti; Muhammad Farhan A (Siber Nusantara Research, 2025)
This study aims to analyze the optimization of public relations activities using the RACE model at PT. Home Credit Indonesia. The RACE model (Reach, Act, Convert, and Engage) is used to analyze each customer journey at Home Credit Indonesia. This study employed a qualitative, descriptive approach, and collected data through observation, interviews, and documentation. The results indicate that PT. Home Credit Indonesia implements various public relations strategies, including digital campaigns, responsive customer service, and financial education programs for customers. These strategies enhance customer service optimization and strengthen support, increase trust, and build loyalty. A challenge faced is managing customer complaints across various communication platforms. This study recommends optimizing digital strategies and increasing personalized interactions to reach more customers.